A novel neuropeptide Y neuronal pathway linking energy state and reproductive behavior. (October 2016) - Muroi, Yoshikage; Ishii, Toshiaki
Abstract: Animals consume energy for reproduction, as well as survival. Excess or insufficient energy investment into reproduction, respectively, threatens the survival of parents or leads to the failure of reproduction. Management of energy consumption in reproduction is important, not only for the success of the process, but also for the survival of the parents. Reproductive behaviors, such as mating and parental behavior, are indispensable for achieving each event of reproduction including gametogamy, parturition, and lactation. Therefore, reproductive behavior is one of the important factors in managing energy consumption for reproduction. Orexigenic and anorexigenic molecules in the hypothalamus have been implicated in the regulation of reproductive functions. An orexigenic neuropeptide, neuropeptide Y (NPY), has been also implicated in the regulation of both reproduction and energy state of animals. In this review, we will first summarize the neuronal mechanism for regulating reproductive functions by orexigenic and anorexigenic molecules in the hypothalamus. Second, we will focus on the NPY neuronal pathways regulating reproductive behavior in the intra- and extra-hypothalamic brain areas. We will highlight the NPY neuronal pathway from the arcuate nucleus to the dorsal raphe nucleus as a novel extra-hypothalamic pathway for energy state-dependent regulation of reproductive behavior. Finally, we will propose a biological significance of the extra-hypothalamic NPY neuronal pathway, which plays an important role in the associative control of feeding and reproductive behaviors. Highlights: Orexigenic and anorexigenic molecules regulate reproductive behavior. NPY signaling into the DRN inhibits maternal behavior and male sexual behavior. The NPY signaling from the Arc coordinates feeding and reproductive behaviors.